MID: a specific database and online platform for male infertility (Journal of Pharmaceutical Negative Results, 2022)
In developing countries, especially like India and China, people have a strong mindset and fully emphasis onchild-bearing. Currently, human male infertility percentage is increasing drastically. Infertility is not a disease andit is treated as a condition with physiological, medical implications. Diagnosis of idiopathic males is difficult thanany other category and it is very hard to find out the reasons for infertility. There are no existing databases tostudy easily about the various genes associated with male infertility. To elucidate the basic knowledge aboutsemen and its composition, various causes, microelements and its role, treatments and genetic causes, as well asto retrieve the basics about the genes and proteins involved with male infertility. MID (Male Infertility Database)was implemented as a web interface using PHP scripting language at backend and HTML, CSS & JavaScript(jQuery Framework) were used at the frontend/client side. The data were collected from the bioinformaticscommon database like PDB, UniProt and Entrez databases. These data were appropriately filtered usingspecialized systematic literature and our previous knowledge on male infertility. The current information aboutmale infertility and updated literature were retrieved from Science direct, Science alert, Goggle Scholar, PubMedand PubMed central. MID provides three modules (“Search”, “Browse” and “Statistics”) that enable searches,acquisition of contents and access to all updated statistical data. The direct links to matching external databasesare also available. The database will be updated at interval corresponding to genes and protein related to maleinfertility. The compilation of all general information, sequence and structural data of all genes and protein in oneplatform is highly useful for current experts and budding researchers in human reproduction and male infertilityarea.